Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s00415-013-7080-2
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging and correlations to Parkinson rating scales

Abstract: The contribution of various brain areas to the overall progression of Parkinson's disease remains to be determined. In this study, we apply MRI diffusion tensor imaging to investigate how alterations in diffusion relate to phenotype and symptoms measured by clinical rating scales. Sixty-four patients were investigated at baseline and three follow-ups (1, 3 and 5 years). Thirty-six patients remained in the last follow-up. Regions of interests included frontal white matter, basal ganglia, thalamus, and cerebellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 56 publications
4
27
2
Order By: Relevance
“…Interestingly, this tract projects from the thalamus to frontal motor areas, including the supplementary motor area, and showed increased MD in freezers in the current study. Similarly, Lenfeldt et al showed that thalamic diffusion differentiated tremor‐dominant from postural‐instability and gait disorder phenotypes. However, the burden of white matter hyperintensities proved not to be different between these phenotypes in a large cohort study …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Interestingly, this tract projects from the thalamus to frontal motor areas, including the supplementary motor area, and showed increased MD in freezers in the current study. Similarly, Lenfeldt et al showed that thalamic diffusion differentiated tremor‐dominant from postural‐instability and gait disorder phenotypes. However, the burden of white matter hyperintensities proved not to be different between these phenotypes in a large cohort study …”
Section: Discussionmentioning
confidence: 94%
“…White matter changes in PD have been consistently linked to Hoehn and Yahr disease staging, self‐efficacy, mental status, and depression . As a much‐investigated biomarker of cognitive decline, white matter abnormalities were also related to the development of executive dysfunction, mild cognitive impairment, and dementia …”
Section: Discussionmentioning
confidence: 99%
“…Lenfeldt et al [] also found that increased UPDRS‐II scale scores were related to increased mean diffusivity in the putamen and the thalamus. The loss of axonal integrity, as well as decreased dopamine uptake in these regions, may help explain the decreased connectivity between the right putamen and the left thalamus.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion tensor imaging (DTI) is a modern MRI technique sensitive to small‐scale brain damage. It measures the diffusion of water molecules, thereby quantifying neuronal integrity, and it has revealed diffusion alterations in several brain areas in PD . Still, its application in segregating phenotypes is limited.…”
Section: Introductionmentioning
confidence: 99%